Optical Coherence Tomography Angiography Analysis of Vessel Density Indices in Early Post-COVID-19 Patients - Chiosi, Flavia; Campagna, Giuseppe; Rinaldi, Michele; Manzi, Gianluigi; dell'Omo, Roberto; Fiorentino, Giuseppe; Toro, Mario; Tranfa, Fausto; D'Andrea, Luca; Rejdak, Magdalena; Costagliola, Ciro (Frontiers in Medicine, 2022)
Purpose: A hypercoagulable state has been reported to cause potential sight-threatening ischemia in patients suffering from Coronavirus disease 2019 (COVID-19). This study aimed to determine whether vessel density (VD), as measured by optical coherence tomography angiography (OCT-A), has insights into retinal and choriocapillaris vascular changes in patients affected by SARS-CoV-2 infection. Methods: 152 patients positive for SARS-CoV-2 infection were enrolled in this observational, retrospective, controlled study. A control group of 60 healthy subjects was selected for statistical comparisons. Raw OCT and OCT-A data were exported and 3D datasets were analyzed to determine VD. Results: 140 eyes (92.1%) were included for final analysis. The VD of the superficial capillary plexus (SCP) did not differ between the two groups. The mean VD of the deep capillary plexus (DCP) and the choriocapillaris (CC) was significantly lower in the foveal sector of the COVID-19 group compared to healthy controls. Within the post-COVID-19 group, the lowest DCP and CC foveal VD values were recorded in patients treated with antiviral therapy; no differences were observed among COVID-19 patients with other comorbidities (hypertension, diabetes, thyroid disease) or taking antiplatelet therapy. DCP and CC foveal VD were significantly lower in patients hospitalized in an intensive care unit (ICU) than asymptomatic patients. Conclusion: Foveal vessel density at the level of DCP and CC was reduced in post-COVID-19 patients. Further studies evaluating these changes over time will be needed to corroborate the hypothesis of a microvascular retinal impairment in individuals who have recently recovered from SARS-CoV-2 infection.